METHODOLOGY FOR ATTRACTING THE INDUSTRIAL BASE OF THE REGION TO MAINTAIN THE FLEET OF EQUIPMENT OF THE BORDER DETACHMENT AT A GIVEN LEVEL OF TECHNICAL READINESS - Holovnia, Serhii (European Science, 2022)
A theoretical study of the process of distribution of maintenance and repair of motor vehicles between the repair unit of the border detachment and car repair organizations was carried out. The work developed: a decision-making model regarding the distri